Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja pada Sekretariat Daerah Kabupaten Bengkulu Tengah - Utami, Tasya Mega (UNIB Press, 2024)
The Central Bengkulu Regent’s Office is a government agency engaged in providing public services. However, there is still suboptimal job satisfaction among its employees. Several factors contribute to this, including work discipline and the work environment. Therefore, the purpose of this study is to examine the impact of work discipline and the work environment on job satisfaction at the Central Bengkulu Regent’s Office. This study employed a census sampling technique, involving 123 employees of the Central Bengkulu Regent's Office. Data collection was conducted using a questionnaire consisting of 14 statements. The analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS version 3.2.9. The results showed that (1) Work discipline has a significant effect on job satisfaction in the Central Bengkulu Regent Office’s; (2) The work environment has a significant effect on job satisfaction in the Central Bengkulu Regent’s Office; For future researchers, it is recommended that this study be used as a reference to address any shortcomings and improve upon the findings. Additionally, it is suggested that the Central Bengkulu Regent’s Office prioritize efforts to enhance job satisfaction by promoting high levels of work discipline and cultivating a positive work environment. Keywords: Work discipline, Work Environment, and Job satisfaction